Pathogenesis, diagnosis and current treatment of prolactinoma: a review of the literature - Szyszka, Monika; Kruszewski, Adrian; Kucharska, Maja; Dąbrowska, Anna; Błaszczak, Karolina; Paduszyńska, Natalia; Przybysz, Paulina (Quality in Sport, 2024)
ABSTRACT: Prolactinoma is a benign tumor of the pituitary gland that leads to the overproduction of prolactin. It is the most common type of pituitary adenoma, accounting for approximately 50% of all pituitary tumors. The clinical presentation of prolactinoma varies depending on the level of prolactin elevation and the size of the tumor. In women, common symptoms include galactorrhea, amenorrhea, and infertility. Men may present with hypogonadism, decreased libido, erectile dysfunction, and gynecomastia. Large prolactinomas, known as macroadenomas, can cause mass effects such as headaches, visual disturbances due to compression of the optic chiasm, and hypopituitarism due to pressure on surrounding pituitary tissue. Understanding the pathogenesis of prolactinoma is crucial for developing effective treatments and improving patient outcomes. The development of prolactinomas involves a complex interplay of genetic, hormonal, and cellular factors. Treatment of prolactinoma aims to normalize prolactin levels, reduce tumor size, and alleviate symptoms. The first-line therapy is dopamine agonists, such as cabergoline and bromocriptine, with surgery and radiotherapy reserved for refractory cases. Furthermore, chemotherapeutic agent - temozolomide may be a treatment of choice in aggressive or malignant prolactinomas. By understanding the underlying mechanisms and different treatment methods, healthcare providers can optimize the management and outcomes for patients with prolactinoma.